2007
DOI: 10.1186/1471-2334-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacteriumendocarditis species-specific risk factors and outcomes

Abstract: Background: Corynebacterium species are recognized as uncommon agents of endocarditis, but little is known regarding species-specific risk factors and outcomes in Corynebacterium endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
76
3
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 83 publications
3
76
3
3
Order By: Relevance
“…The age of this patient was in agreement with previous reports, where 80% patients suffering from NTCD endocarditis were under 30 years of age [6][7][8]11,22]. Several predisposing factors for NTCD infections have been identified; these include intravenous drug use, low socioeconomic conditions, alcoholism, homelessness, diabetes mellitus, hepatic cirrhosis, and dental caries in addition to immune-compromised status [6,7,12,22]. However, there is enough evidence suggesting that NTCD infections can occur in persons with no identifiable predisposing factors or concomitant diseases [7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The age of this patient was in agreement with previous reports, where 80% patients suffering from NTCD endocarditis were under 30 years of age [6][7][8]11,22]. Several predisposing factors for NTCD infections have been identified; these include intravenous drug use, low socioeconomic conditions, alcoholism, homelessness, diabetes mellitus, hepatic cirrhosis, and dental caries in addition to immune-compromised status [6,7,12,22]. However, there is enough evidence suggesting that NTCD infections can occur in persons with no identifiable predisposing factors or concomitant diseases [7].…”
Section: Discussionsupporting
confidence: 92%
“…However, there is enough evidence suggesting that NTCD infections can occur in persons with no identifiable predisposing factors or concomitant diseases [7]. The presence of a prosthetic heart valve appears to be the most likely predisposition in this case, as a number of studies have reported that patients with valve replacement, preexisting cardiac disease, or abnormalities are at a higher risk for having Corynebacterium IE [4,7,11,22]. NTCD endocarditis has been described as an aggressive and destructive disease with frequent thrombo-embolic complications [10,11], which were also observed in this patient.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Los autores documentaron 14 casos de endocarditis por C. striatum en los que esta especie fue significativamente más frecuente en adultos que en niños; en la mayoría de los casos fue de origen nosocomial y se presentó como la especie con mayor tasa de supervivencia. No se encontraron, sin embargo, diferencias significativas en cuanto a sexo y la patología grave subyacente 33 .…”
Section: Discussionunclassified
“…Paviour et al (2002) described the isolation of C. amycolatum strains from three patients with mastitis. A meta-analysis of 129 cases of Corynebacterium endocarditis involving nine species revealed that only C. amycolatum has a predilection for women (Belmares et al, 2007). The majority of infections due to C. amycolatum were in either immunocompromised patients or patients with intravascular devices (De Miguel-Martinez et al, 1996;Berner et al, 1997;Vaneechoutte et al, 1998;De Miguel et al, 1999;Oteo et al, 2001;Knox & Holmes, 2002;Chiu et al, 2005;Adderson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%